Oxygen A-band absorption spectroscopy with solar photon counting and lithium niobate nanophotonic circuits - Zhang, Jiuyi; Sua, Yong Meng; Hu, Yongxiang; Ramanathan, Jeevanandha; Huang, Yu-Ping (Frontiers in Remote Sensing, 2022)
Oxygen A-band measurements can provide important information about cloud top height, cloud physical and optical thickness, and surface atmospheric pressure. So far, O2 A-band measurements are typically made with spectrometers at a spectral resolution of 40 pm (such as in the OCO-2 satellite) or a coarser resolution. This paper reports a new CubeSat measurement concept with higher spectral resolution over the O2 A-band using integrated photonic circuits and solar photon counting techniques. An integrated Micro-ring filter (MRR) chip with 10~pm resonant linewidth with an extinction ratio of 25 dB or higher is designed, fabricated, and used for precise measurements of the atmospheric oxygen A-band absorption line-shapes around 770 nm. With solar-photon counting and using a narrow-band filter made of an integrated, fast-swept MRR on LNOI, we have demonstrated a high-resolution measurement of the O2 A-band absorption spectrum, exhibiting good agreement with the HITRAN database.